Optimal Delay and Lifetime Aware Depth Based Routing for Underwater Optical Wireless Sensor Networks - et. al., Meenu Rani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Underwater optical wireless sensor network (UOWSN) is an emerging technology in the wireless sensor network that has been used for different applications are natural catastrophe advance warning devices, tracking biodiversity, oil boiling and government surveillance. Although electromagnetic or optical waves could be used for communicating submerged, for realistic UOWSN such approaches are not necessary. The electromagnetic transmission via liquid ammonia promotes only at large distances with lower frequencies because of signal integrity. UOWSN faces several issues like restricted bandwidth, increased propagation delay, irregular node mobility which affects the routing behaviours in such environment. We suggest an effective mechanism on distance dependent routing (ODLDR) lag and lifespan in this article for UOWSN. First, we introduce group partitioning algorithm for cluster formation that reduce the use of resources of network. Second, an efficient priority based scheduling algorithm proposed for trust computation, which finalize the CH and routing path. The simulation results show that the effectiveness of proposed ODLDR protocol package delivery rate, tracking reliability, side-to-end lag, transmission and service life in terms of resource usage.